2021
DOI: 10.3390/catal11081002
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable One-Pot Immobilization of Enzymes in/on Metal-Organic Framework Materials

Abstract: The industrial use of enzymes generally necessitates their immobilization onto solid supports. The well-known high affinity of enzymes for metal-organic framework (MOF) materials, together with the great versatility of MOFs in terms of structure, composition, functionalization and synthetic approaches, has led the scientific community to develop very different strategies for the immobilization of enzymes in/on MOFs. This review focuses on one of these strategies, namely, the one-pot enzyme immobilization withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 109 publications
1
14
0
Order By: Relevance
“…The immobilized domain showed affinity toward substrate compared to the free domain, which could be due to conformational changes in enzyme that may change the microenvironment of enzyme and result in greater accessibility of substrate to the active site of the enzyme 37 . Similar results of increased affinity of the immobilized enzyme toward substrate have been reported in many studies 38,39 …”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The immobilized domain showed affinity toward substrate compared to the free domain, which could be due to conformational changes in enzyme that may change the microenvironment of enzyme and result in greater accessibility of substrate to the active site of the enzyme 37 . Similar results of increased affinity of the immobilized enzyme toward substrate have been reported in many studies 38,39 …”
Section: Discussionsupporting
confidence: 71%
“…37 Similar results of increased affinity of the immobilized enzyme toward substrate have been reported in many studies. 38,39 The kinetic studies indicated a decrease in K m for immobilized trypsin-like domain indicating better substrate affinity. 40 Bornscheuer 41 showed that immobilization modifies the active site of the enzyme thus reducing its K m value.…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme immobilization is an effective method to improve the stability of bioscavengers. Specifically, multiple strategies, such as adsorption, covalent bonding, encapsulation, and copolymerization, can be used to physically attach enzymes to a solid support (carrier) to isolate enzymes from aggressive environments. Mesoporous metal–organic frameworks (MOFs) have emerged as advanced materials for enzyme immobilization due to their tunable size, high surface area, and possible biofunctionalization. These special properties endow MOFs with high enzyme loading, stable catalytic activity, and excellent diffusion of both substrate and product . Zeolitic imidazole framework-8 (ZIF-8), formed by coordination between 2-methylimidazole and Zn 2+ ions, is a typical and excellent MOF material for one-pot enzyme encapsulation with mild synthesis conditions and good biocompatibility and stability. , However, clearance by the immune system is still one of the major issues of enzyme/MOF nanoparticles, which may lead to attenuation of enzyme activity, necessitating further functionalization of these nanoparticles. , …”
Section: Introductionmentioning
confidence: 99%
“…There are three general approaches for the preparation of MOF-based enzyme composites: surface attachment, post-synthetic diffusion, and encapsulation [3][4][5][6][7]. Either a surface attachment can be made by physical adsorption, or an enzyme can be grafted onto the MOF's surface (covalent or supramolecular attachment).…”
Section: Introductionmentioning
confidence: 99%